STRATEGI PENGEMBANGAN PAGUYUBAN KELUARGA DAN PEDAGANG TANAMAN HIAS, SEBAGAI “ LEMBAGA KOPERASI PRIMER “ KAMPUNG WISATA BUNGA, DI DESA BANYUURIP, KEC. KEDAMEAN, KAB. GRESIK - Sri Andayani; Sumiati Sumiati (STIE Mahardhika, 2022)
Situation analysis Gresik Regency is one of the regencies in East Java, which used to be very well known as an industrial city because there are many industrial companies, one of which is